A filled organic crystal as a hybrid large-bandwidth optical waveguide. Issue 34 (8th April 2019) - Catalano, Luca; Commins, Patrick; Schramm, Stefan; Karothu, Durga Prasad; Rezgui, Rachid; Hadef, Kawther; Naumov, Panče
Abstract : A 9, 10-dicyanoanthracene hollow crystal was filled with a perylene diimide derivative with complementary emissive features and successfully tested as a hybrid optical waveguide. Abstract : A fluorescent hollow crystal of 9, 10-dicyanoanthracene was filled with a perylene diimide derivative with complementary emissive features. The obtained crystal-in-crystal hybrid was used as a multiresponsive optical waveguide, which showed passive and active modes of light transduction and a bandwidth that extends from the visible to the infrared region.